Sociodemographic and Lifestyle Determinants of Plasma Oxidative Stress Markers 8-OHdG and F2-Isoprostanes and Associations with Metabolic Syndrome. (23rd February 2016) - Black, Catherine N.; Bot, Mariska; Scheffer, Peter G.; Penninx, Brenda W. J. H.
Abstract : Background. Oxidative stress is increasingly important in health research. Therefore, it is necessary to understand which factors determine basal oxidative stress. This study examines the associations of various determinants with markers of oxidative DNA and lipid damage: 8-hydroxy-2′-deoxyguanosine (8-OHdG) and F2-isoprostanes. Methods. Data are from the Netherlands Study of Depression and Anxiety; 1117 subjects (18–65 years) without a current psychiatric diagnosis. Multivariable regression analyses were conducted with plasma levels of 8-OHdG and F2-isoprostanes (measured by LC/MS-MS) including sociodemographic, lifestyle, and sampling variables. Associations with metabolic syndrome (MetS) and chronic disease were examined. Results. 8-OHdG and F2-isoprostanes were weakly correlated (r = 0.06, p = 0.045). Both were positively associated with age and cotinine (cigarette exposure); 8-OHdG was lower in females and after longer sample storage. F2-isoprostanes were higher in females, alcohol users, and in samples collected in spring and lower in supplement users and those with more education. Both markers were lower in fasting subjects. F2-isoprostanes, not 8-OHdG, were positively associated with MetS. Conclusion. The weak correlation between 8-OHdG and F2-isoprostanes suggests they reflect specific aspects of oxidative stress. Both markers are associated with a range of sociodemographic, lifestyle, and sampling determinants which should be considered in future research. F2-isoprostanes are associated with MetS.